The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s12888-019-2420-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in response to war-related trauma and posttraumatic stress disorder – a study among the Congolese refugees in Uganda

Abstract: Background: The wars in the Democratic Republic of Congo have left indelible marks on the mental health and functioning of the Congolese civilians that sought refuge in Uganda. Even though it is clear that civilians who are exposed to potentially traumatizing events in war and conflict areas develop trauma-related mental health problems, scholarly information on gender differences on exposure to different war-related traumatic events, their conditional risks to developing PTSD and whether the cumulative exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 37 publications
5
47
3
Order By: Relevance
“…Particularly at high levels of trauma load, interindividual variability in PTSD risk is low, as almost everybody will develop PTSD (Neuner et al, 2004 ). Indeed, a recent investigation among Congolese refugees found sex differences in PTSD risk and reported that in the subgroup with very high trauma exposure, the differences between females and males vanished (Ainamani et al, 2020 ). Accordingly, sex differences in PTSD risk might be less pronounced in war-torn samples with high levels of trauma load due to ceiling effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly at high levels of trauma load, interindividual variability in PTSD risk is low, as almost everybody will develop PTSD (Neuner et al, 2004 ). Indeed, a recent investigation among Congolese refugees found sex differences in PTSD risk and reported that in the subgroup with very high trauma exposure, the differences between females and males vanished (Ainamani et al, 2020 ). Accordingly, sex differences in PTSD risk might be less pronounced in war-torn samples with high levels of trauma load due to ceiling effects.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, it has often been argued that the higher PTSD risk in females can at least be partially accounted by the increased exposure to sexual violence (Gavranidou & Rosner, 2003 ). In the aforementioned study of Congolese refugees with pronounced PTSD prevalence, females had a higher risk than males of developing PTSD when considering trauma load (Ainamani et al, 2020 ). However, it has to be noted that 56% of the interviewed females reported the experience of rape, compared to 15% of males.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we found that post-migration stress seems to be a subtler but persistent character as compared with previously experienced traumatic events, which tend to be sudden and traumatic. Post-migration stress and mental ill health are in the other hand likely to be reciprocally associate in the resettlement phase: it could be explained both for the effect of post-migration traumatic events and for the impact of traumatic events occurred before migration and during initial migration phases that could make refugees particularly vulnerable to psychological suffering even after resettlement [9,18]. Giacco, who recently critically analysed the literature on this topic, identified three different time points in the post migration phase, each of them with a relevant association with mental health: initial settlement in the host country, integration in the host country and challenges to or revocation of the immigration status [6].…”
Section: Discussionmentioning
confidence: 99%
“…These results expand previous findings that were limited to women or Syrian populations of asylum seekers and refugees [ 7 9 ]. As compared with women, men may be exposed to different trauma experiences, such as seeing someone being tortured by soldiers or having been imprisoned [ 18 ], and may also react differently to similar stressors. Similarly, there might be differences across different ethnic groups [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation